Development of Interactive Multimedia Using Articulate Storyline 3 to Enhance Learning Outcomes in Creative Fabric Lessons at a Vocational High School - Shofi, Amalia; Wahyuningsih, Sri Endah; Anis, Samsudin (Universitas Negeri Semarang, 2025)
This study aimed to develop interactive multimedia based on Articulate Storyline 3 and to test its feasibility, practicality, and effectiveness in teaching Creative Fabric to students in the Fashion Design Expertise Program at SMK Negeri 1 Purwodadi. The research method employed was Research and Development (R&D) using the ADDIE development model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The experimental research design used was a Pretest-Posttest Control Group Design, involving 60 11th-grade students divided into an experimental and a control class. The results showed that the developed interactive multimedia had a very high feasibility level, with 92.27% approval from media experts and 87.69% approval from material experts. The practicality test conducted by 10 teachers yielded a score of 86.94%, which falls into the